Pulsatile Chronotherapeutic Drug Delivery for Controlling Early Morning Surge in Blood Pressure; Effect of Coating on Eplerenone In-vitro, In-vivo Release and Urinary Na/K Ratio - Maha Abd El hameed Marzouk; Manal Kamal Darwish; Ghada Ehab Yassin; Marwa Adel Abd El-Fattah (Universidade de São Paulo, 2022)
Abstract The objective of the present study was to develop time delayed chronotherapeutic formulation of Eplerenone (Ep) to provide rapid drug release after a pre-determined lag time for the treatment of early morning hypertension. Cyclodextrin complexation was used to prepare fast release Ep core tablets. The developed core tablets were then coated with different rate-controlling polymers using compression coating technique. The developed tablets were evaluated for hardness, friability, drug content and swelling index. The in-vitro drug release was carried out to study the effect of different coating materials on drug release and lag time. Tablets selected for stability study were those showing lag time of 5-7 hours followed by complete drug release; F2, F3, F7, F8, and F12. The in-vivo study was carried out on tablets with the highest t90 as compared to commercial tablets after being administered to healthy human volunteers where plasma Ep and urinary Na/K ratio were determined. Results suggested that this approach was able to provide delayed release Ep formulations that will be useful for patients with morning surge in blood pressure.